TWO NEW SPECIES OF PAVANELLIELLA (MONOGENEA, DACTYLOGYRIDAE) PARASITIC ON PIMELODID FISHES FROM MOGI GUAÇU RIVER, SOUTHEASTERN BRAZIL, AND NOTES ON THE MORPHOLOGY OF P. PAVANELLII - Aguiar, Julio C. (2011)
Two new species of Pavanelliella (Dactylogyridae) were described and some details about the morphology of Pavanelliella pavanellii Kritsky & Boeger, 1998 were added based on specimens collected from pimelodid fishes from Mogi Guaçu River, Brazil. Pavanelliella takemotoi sp. n., collected from nasal cavities of Pimelodus maculatus Lacepède, 1803 differs from its congeners by having a male copulatory organ (MCO) with 2–5 rings, vaginal canal sinuous without loops in distal portion of vaginal canal and anteriorly directed vagina containing five irregular rings around the vestibule. Pavanelliella laertei sp. n. collected from P. heraldoi Azpelicueta, 2001 is separated from the other species of the genus by lacking a vaginal vestibule and by distal end shape of accessory piece, which resemble flames or is bifurcated with one flank hooked in P. laertei sp. n. The specimens of P. pavanellii examined in this study showed morphological variations especially on MCO, vaginal canal and vagina morphology with respect to the holotype and paratype and are noted in this paper. Significant differences among the described species were confirmed on the light of multivariate morphometric statistical analysis. Initially a Principal Component Analysis (PCA) showed the multivariate distinction between the three species and after a Linear Discriminant Analysis (LDA) revealed that the Maximum number of MCO ring and the MCO length fairly contributed to the discrimination between all Pavanelliella species (Wilk´s lambda = 0.006; p<0.000). This is the first record of Pavanelliella species in Mogi Guaçu River.